Insights into enzymatic degradation of physically crosslinked hydrogels anchored by functionalized carbon nanofillers. (20th January 2022) - Nair, Adwaita SR; Devi, Sudeepa; Mandal, Subhash; Tripathi, Upendra K.; Roy, Debmalya; Prasad, N. Eswara
Abstract : Immobilization of hydrophobic enzymes on the surface of nanofillers disturbs the non-covalent interactions of polymer–filler networks and destabilizes physically crosslinked hydrogels. Abstract : The effect of different geometries of functional carbon nanofillers has been studied to understand the nature of enzymatic degradation of physically crosslinked hydrogels. The noncovalent interactions between the polymer and filler phases were studied in order to investigate the stability of interpenetrating network structures of hybrid hydrogels. The exposed surface of the embedded nanomaterials in a polymeric matrix was found to be very critical for interactions with enzymes, which lead to an increase in the enzymatic degradation of nanocomposite hydrogels. The zero, one, two and hierarchically arranged functional nanomaterial anchored crosslinked polymeric networks were used to gain insights into the non-bonded electronic interactions by enzyme immobilization. The amount of functionalized nanofillers and degradation time were varied to establish that nanomaterials in the physically crosslinked polymeric network showed insignificant cytotoxicity on the lysozyme enzyme. The immobilization and physical interactions of the adsorbed enzymes with functional nanofillers were found to have a profound role in disintegration of crosslinked hydrogel networks reinforced by nanofillers. The structure–property studies of nanocomposite hydrogels for biodegradability may lead to the design of high-performance biomedical devices.